1966
DOI: 10.1039/j29660000849
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies of oxidation. Part VIII. Elimination reactions of some hydroxyalkyl radicals

Abstract: The electron spin resonance spectra of radicals generated by the one-electron oxidation of some diols and related compounds are described and discussed. Evidence is adduced that radicals of the type HO-k-d-x, where X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Such a value for this rate constant is consistent with the unrearranged radical being the dominant species at high rates of initiation, as in the e.s.r. experiments (15,16), but the rearranged radical being dominant at low rates of initiation. If the rearrangement is also acid-catalyzed, [Ic], eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a value for this rate constant is consistent with the unrearranged radical being the dominant species at high rates of initiation, as in the e.s.r. experiments (15,16), but the rearranged radical being dominant at low rates of initiation. If the rearrangement is also acid-catalyzed, [Ic], eq.…”
mentioning
confidence: 99%
“…The yield of acetaldehyde (G - 15) suggested that a chain reaction was involved but -it was the nature of this product which evoked our curiosity. Acetaldehyde cannot be represented as a product of the oxidation of ethylene glycol.…”
mentioning
confidence: 99%
“…It can be seen that there is very little difference between the slopes of the three lines but there is a significant change in the intercept. Even when radical-radical reaction [7] is omitted, the steady state method yields an extremely com- constant during the experiment, the expression simplifies to A plot of I/@,,, + us. 1/[Fe3 + ] (inset Fig.…”
Section: Results and Disc~ssisnmentioning
confidence: 99%
“…The O=CH-CH, radical would then abstract hydrogen from another ethylene glycol to produce acetaldehyde. Both these radicals have been shown to be present by electron spin resonance spectroscopy (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the radical from propylene glycol is CH2COCH3 , and that by analogy, the triplet sp ectrum from ethylene glycol belon gs to th e radical CH2CHO. " Similar arguments have appeared recently [28,29]. Although a molecular orbital account will not be attempted, allylic resonance structure s can be written for the se radicals,…”
mentioning
confidence: 99%